Applied International Corporate Finance: - Ernst, Dietmar; Häcker, Joachim (Vahlen, 2012)
Corporate Finance in der Praxis.The authors present all core aspects of Corporate Finance: M&A, Private Equity, Acquisition Financing, IPO, and Going Private. Furthermore, the techniques Due Diligence and Valuation are scrutinised. The book includes various case studies, which help to get a practical understanding and apply the techniques in the user´s day-to-day business. Investment bankers, lawyers, accountants, experts working in strategic departments, consultants, shareholders, management professionals, professors, and students seeking in-depth knowledge of Corporate Finance will profit from the book`s practice oriented approach.The information supplement includes- for students: samples of final written examinations- for professors: Excel solutions for the final written examinations as well as a course syllabus- for business professionals: a fully integrated Excel valuation model covering all spreadsheets analyzed in the valuation section of this bookThe authorsDr. Dr. Dietmar Ernst is Professor for International Finance at Nürtingen University (Germany) and Director of the German Institute of Corporate Finance.Dr. Dr. Joachim Häcker is Professor for Finance at Munich University, the University of Louisville (USA), as well as Director of the German Institute of Corporate Finance.